Whole genome sequence and comparative genomic sequence analysis of Helicoverpa armigera nucleopolyhedrovirus (HearNPV-L1) isolated from India - Raghavendra, Ashika T. (Virusdisease, 2017)
The whole genome of Helicoverpa armigera nucleopolyhedrovirus (HearNPV) from India, HearNPV-L1, was sequenced and analyzed, with a view to look for genes and/or nucleotide sequences that might be involved in the differences and virulence among other HearNPVs sequenced from other countries like SP1A (Spain), NNg1 (Kenya) and G4 (China). The entire nucleotide sequence of the HearNPV-L1 genome was 136,740 bp in length having GC content of 39.19% and contained 113 ORFs that could encode polypeptides with more than 50 amino acids (GenBank accession number KT013224). Two ORFs, viz., ORF 18 (300 bp) and ORF 19 (401 bp) identified were unique in HearNPV-L1 genome. Most of the HearNPV-L1 ORFs showed high similarity to NNg1, SP1A and G4 genomes. HearNPV-L1 genome contains 5 h (hr1-hr5), these regions were found 84–100% similar to hr region of NNg1, SP1A and G4 genomes. A total of four bro genes were observed in HearNPV-L1 genome, of which bro-a gene was 12 and 351 bp bigger than SP1A and G4 bro-a, respectively, while bro-b was 15 bp bigger SP1A and NNg1 bro-b, whereas 593 bp shorter than G4 bro-b, while bro-c was 12 bp shorter than NNg1, however bro-c was absent in G4 genome. HearNPV-L1 bro-d was 100% homologous to bro-d of SP1A, NNg1 and G4 genomes, respectively. The comparative analysis of HearNPV-L1 genome indicated that there are several other putative genes and nucleotide sequences that may be responsible for insecticidal activity in HearNPV-L1 isolate, however, further functional analysis of the hypothetical (putative) genes may help identifying the genes that are crucial for the virulence and insecticidal activity. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13337-016-0352-6) contains supplementary material, which is available to authorized users.